Actions of the NLRP3 and NLRC4 inflammasomes overlap in bone resorption. Issue 9 (12th August 2021) - Alippe, Yael; Kress, Dustin; Ricci, Biancamaria; Sun, Kai; Yang, Tong; Wang, Chun; Xiao, Jianqiu; Abu‐Amer, Yousef; Mbalaviele, Gabriel
Abstract: Overwhelming evidence indicates that excessive stimulation of innate immune receptors of the NOD‐like receptor (NLR) family causes significant damage to multiple tissues, yet the role of these proteins in bone metabolism is not well known. Here, we studied the interaction between the NLRP3 and NLRC4 inflammasomes in bone homeostasis and disease. We found that loss of NLRP3 or NLRC4 inflammasome attenuated osteoclast differentiation in vitro. At the tissue level, lack of NLRP3, or NLRC4 to a lesser extent, resulted in higher baseline bone mass compared to wild‐type (WT) mice, and conferred protection against LPS‐induced inflammatory osteolysis. Bone mass accrual in mutant mice correlated with lower serum IL‐1β levels in vivo. Unexpectedly, the phenotype of Nlrp3 ‐deficient mice was reversed upon loss of NLRC4 as bone mass was comparable between WT mice and Nlrp3;Nlrc4 knockout mice. Thus, although bone homeostasis is perturbed to various degrees by the lack of NLRP3 or NLRC4, this tissue appears to function normally upon compound loss of the inflammasomes assembled by these receptors.